2016
DOI: 10.25145/j.pasos.2016.14.071
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Creative tourism in Portugal

Abstract: Abstract:A new paradigm in the tourism industry is changing the meaning of culture and its use in promoting several touristic products/experiences and destinations. The questions we want to answer are the following: How can creative tourism be important in a destination and what are its implications in its organization? Methodology was based on the bibliographic review related to the object of study, data and content analysis, "snowball sampling" technique, surveys and participant observation technique. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 6 publications
1
16
0
8
Order By: Relevance
“…With the diffusion of the concept of prosumer – a fusion of the words “producer” and “consumer” – since that time, the consumer has become the producer of many of the products and experiences he consumes. The diffusion of this concept coincides with the emergence of a new generation of tourists, also called “qualified consumers” or “creative consumers” ( Carvalho, Ferreira, & Figueira, 2016 ; Mihajlović & Koncul, 2016 ; Pappalepore, Maitland, & Smith, 2014 ; Richards, 2010a ; Richards & Wilson, 2006 ; Zhang & Yu, 2018 ), postmodern travellers ( Carvalho et al, 2016 ; Jelinčić & Žuvela, 2012 ; O’Dell, 2007 ; Pappalepore et al, 2014 ; Tan, Luh, & Kung, 2014 ) or “creative tourists” ( Raymond, 2003 ; Smith, 2016 ; Tan et al, 2014 ; Zhang & Yu, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the diffusion of the concept of prosumer – a fusion of the words “producer” and “consumer” – since that time, the consumer has become the producer of many of the products and experiences he consumes. The diffusion of this concept coincides with the emergence of a new generation of tourists, also called “qualified consumers” or “creative consumers” ( Carvalho, Ferreira, & Figueira, 2016 ; Mihajlović & Koncul, 2016 ; Pappalepore, Maitland, & Smith, 2014 ; Richards, 2010a ; Richards & Wilson, 2006 ; Zhang & Yu, 2018 ), postmodern travellers ( Carvalho et al, 2016 ; Jelinčić & Žuvela, 2012 ; O’Dell, 2007 ; Pappalepore et al, 2014 ; Tan, Luh, & Kung, 2014 ) or “creative tourists” ( Raymond, 2003 ; Smith, 2016 ; Tan et al, 2014 ; Zhang & Yu, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, tourist demand has become increasingly exacting, segmented and constantly changing (Fundação de Serralves, 2008 ; Tan et al, 2014 ; Carvalho et al, 2016 ; Smith, 2016 ; Zhang & Yu, 2018 ). This process points to the emergence of a new tourist profile and, consequently, a new pattern of consumption that is directed toward the use of creativity as an alternative to mass cultural tourism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the low density of some areas on the map, several issues appear to be underresearched or in an embryonic phase, namely the role of co-creation between organizations and tourists inside Cluster E (Ross et al, 2017; Zatori, 2016), the identification of a concrete way which creative tourism activities can improve urban tourism within Cluster C (Carvalho, Ferreira, & Figueira, 2016; Marques & Borba, 2017; Wattanacharoensil & Schuckert, 2016) and the new concept of the participatory tourism experience in Cluster B (de Bruin & Jelincic, 2016; Everingham, 2015). The results allow some opportunities for future research on creative tourism to be identified.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Ďalším súvisiacim problémom bola absencia oficiálnej webovej stránky hradu na internete ako oficiálnej "virtuálnej brány" na hrad. Pre návštevníka v cestovnom ruchu je dnes internet hlavným zdrojom informácií o cestovných cieľoch, podľa španielskeho cestovateľského portálu hosteltur.com (Carvalho et al, 2016) ľudia navštívia v priemere až 23 webových stránok pred výberom svojej turistickej destinácie. Pri zadaní kľúčového hesla "Bratislavský hrad" alebo "Bratislava Castle" internetový prehliadač ponúka linky na rôzne stránky (tab.…”
Section: Prieskum Návštevnosti Bratislavského Hradu a Historického Múunclassified